Comparative Analysis Spindle Speed Constant with Cutting Speed Constant against Surface Roughness Gradual Turning Steel ST 37 on the NC PU 2A Machine - Efendi, Defindo; A, Yufrizal; K, Arwizet (Teknomekanik, 2018)
Parameters of spindle speed and cutting speed affect surface roughness in the turning process. The purpose of this research is to know the comparison of the level surface roughness resulting from the parameters of spindle speed constant and cutting speed constant. The method of this research is experimental research, by performing gradual turning process on the steel ST 37 specimens in the NC PU 2A EMCOTURN 120 machine. The number of specimens is 6 specimens, each specimen is gradual turned as much 3 levels, each level is tested as much 3 points of surface quality using "Surface Tester Mitutoyo SJ-201P". The results of the research were analyzed using descriptive statistics by taking the average value of the two parameters. Based on the analysis of the data from the results of the research conducted, the surface roughness produced using a cutting speed constant (G96) is better than the spindle speed constant (G97). Cutting speed constant is more stable when cutting in gradual turning.